Pemalsuan Hadis Dan Upaya Mengatasinya - Alamsyah Alamsyah (Universitas Islam Negeri Alauddin, 2013)
The existence of the false hadis is a real fact in Islamic history. There are some motives why one made the false hadis addressing to Prophet Muhammad. Thus, it is hard to differenciate between the false hadis and the true one. Therefore, ulamas have made the basic rules in determining the true hadis, hasan and weak hadis. To know the quality of hadis can be identified from its sanad and matan.